Exploring the Impacts of Green Accounting, Sustainability Report Disclosure, and Environmental Investment on Financial Performance - Saenggo, Alexandra Theresia Pureheart; Widoretno, Astrini Aning (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
The operational activities of companies produce hazardous waste, frequently leading to environmental pollution. In fact, companies also have an obligation to maintain and protect the environment. This primary objective of this study is to examine the effect of green accounting, disclosure of sustainability reporting, and environmental investment on company’s financial performance. This study uses a quantitative approach with a population of companies in the mining and medical sectors listed on the Indonesia Stock Exchange (IDX) during 2021-2022. The analysis technique used is multiple linear regression analysis. The sample of this study consisted of 64 energy and healthcare companies that met certain criteria, using purposive sampling techniques, so that the total sample analyzed was 64 companies with 128 observations. The results showed that sustainability reporting and environmental investment affects the company's financial performance, while green accounting has no effect on the company's financial performance. The implication of this study shows the importance of companies in improving the company's image which will indirectly impact on improving the company's financial performance through environmental investment and sustainability reporting.